1997
DOI: 10.1038/sj.onc.1201315
|View full text |Cite
|
Sign up to set email alerts
|

Cytostatic effect of TNFα on cancer cells is independent of p21WAF1

Abstract: Tumor necrosis factor a (TNFa) is a cytotoxic/cytostatic compound for a variety of human cancer cells. The p21 WAF1 protein is a cyclin-dependent kinase inhibitor (CDKI) that binds to cyclin/cyclin-dependent kinase (CDK) complexes and inhibits their kinase activities, thereby leading to cell cycle arrest. We found that the cytostatic eect of TNFa on the cervical cancer cell line, ME180, was concomitant with an arrest of these cells in the G0/G1 phase of the cell-cycle. This corresponded with an increase in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…In different cellular models, other investigators have found that p21/Waf1 is not required to induce G1-arrest in response to TNFa. Shiohara et al 51 have shown that overexpression of p21/Waf1 antisense in ME-180 cells does not abrogate TNFa-dependent G1-growth arrest. Additionally, Nalca and Rangnekar 52 have demonstrated that interleukin-1 (IL-1), another cytokine promoting cytostatic effects, induces p53 and p21/Waf1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In different cellular models, other investigators have found that p21/Waf1 is not required to induce G1-arrest in response to TNFa. Shiohara et al 51 have shown that overexpression of p21/Waf1 antisense in ME-180 cells does not abrogate TNFa-dependent G1-growth arrest. Additionally, Nalca and Rangnekar 52 have demonstrated that interleukin-1 (IL-1), another cytokine promoting cytostatic effects, induces p53 and p21/Waf1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…6,25 In this study, U87 cells depleted of either p53 or p21 did not develop a senescent phenotype, but instead remained cytostatic as opposed to triggering apoptosis in response to activated AKT. 26,27 In addition, acute PTEN inactivation induces growth arrest through the p53-dependent cellular senescence pathway both in vitro and in vivo. 28 PTEN/AKT might exert another regulatory function(s) of cell proliferation through a p53/p21-independent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Among these are both mitogenic and antimitogenic activities. [64][65][66] Cell division and tissue repair occur as events opposing injury and can limit the extent of liver injury. 36,37 That is, cell proliferation can afford protection whereas a lack of proliferation can increase injury.…”
Section: Discussionmentioning
confidence: 99%